When viral invasion meets vascular catastrophe: A case report of herpes simplex virus-related stroke (Indian Journal of Case Reports, 2026)
Herpes simplex virus (HSV) encephalitis is the most common viral encephalitis in industrialized nations, typically affecting the temporal lobes. While seizures are frequent complications, cerebrovascular events such as hemorrhagic stroke are rare. We report an 85-year-old man with multiple comorbidities who presented with altered mental status and progressive weakness. Cerebrospinal fluid analysis confirmed HSV-1 DNA, and neuroimaging revealed diffuse microbleeds and a left cerebellar hematoma. The patient was managed conservatively with intravenous acyclovir and antibiotics, showing gradual improvement, and was discharged in stable condition. This case highlights the unusual occurrence of cerebellar hemorrhage in HSV encephalitis, likely due to necrotizing vasculitis and immune-mediated vascular injury. Awareness of such vascular complications is essential for timely diagnosis and management. Early antiviral therapy, supportive care, and close monitoring can improve outcomes, even in elderly patients with significant comorbidities